If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3a + -7) = 0 Reorder the terms: 2(-7 + 3a) = 0 (-7 * 2 + 3a * 2) = 0 (-14 + 6a) = 0 Solving -14 + 6a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 6a = 0 + 14 Combine like terms: -14 + 14 = 0 0 + 6a = 0 + 14 6a = 0 + 14 Combine like terms: 0 + 14 = 14 6a = 14 Divide each side by '6'. a = 2.333333333 Simplifying a = 2.333333333
| 2/5x-3/10x=3 | | -(6y-5)-(5y-6)=0 | | y^2+64= | | (3x-6)=(8x-9) | | 28-2(x+2)=12x | | 9/10k=10.8 | | 3x+x-5=3 | | 8(9x-8)=8(3x+10) | | -20z^5+40z^4+25z^3=0 | | (x-7)(x+6)=-6(x+3) | | 2/5/2/3 | | 4x+4=9x+36 | | 3/8x-1/3x=1/6x | | (7v-3)(8v+5)= | | 7/8n=9.625 | | 25-(4/3)x=5 | | 33/25*10/117*22/22 | | 12y/3x | | (19b-2)-9(2b+4)=-3 | | -15x^2+120x+10=115 | | x^2-24x=10x | | 5/6x=7 | | 33/25x10/117x27/22 | | 0=2x^3-5x^2-6x+15 | | 9x+5x+3+8=8x+4+5x | | 6x-9=57 | | 8+4r-7=8r+9-3r | | 6x+2=10+4x | | -6x-9=27 | | 3x+5(2x-9)=98 | | 4X+3+6X-1=-6+4X+2+9 | | x+4+x+4(8x+4)=122 |